A shear stress micromodel of urinary tract infection by the Escherichia coli producing Dr adhesin. - Beata Zalewska-Piątek; Marcin Olszewski; Tomasz Lipniacki; Sławomir Błoński; Miłosz Wieczór; Piotr Bruździak; Anna Skwarska; Bogdan Nowicki; Stella Nowicki; Rafał Piątek (PLoS Pathogens)
In this study, we established a dynamic micromodel of urinary tract infection to analyze the impact of UT-segment-specific urinary outflow on the persistence of E. coli colonization. We found that the adherence of Dr+ E. coli to bladder T24 transitional cells and type IV collagen is maximal at lowest shear stress and is reduced by any increase in flow velocity. The analyzed adherence was effective in the whole spectrum of physiological shear stress and was almost irreversible over the entire range of generated shear force. Once Dr+ E. coli bound to host cells or collagen, they did not detach even in the presence of elevated shear stress or of chloramphenicol, a competitive inhibitor of binding. Investigating the role of epithelial surface architecture, we showed that the presence of budding cells-a model microarchitectural obstacle-promotes colonization of the urinary tract by E. coli. We report a previously undescribed phenomenon of epithelial cell "rolling-shedding" colonization, in which the detached epithelial cells reattach to the underlying cell line through a layer of adherent Dr+ E. coli. This rolling-shedding colonization progressed continuously due to "refilling" induced by the flow-perturbing obstacle. The shear stress of fluid containing free-floating bacteria fueled the rolling, while providing an uninterrupted supply of new bacteria to be trapped by the rolling cell. The progressive rolling allows for transfer of briefly attached bacteria onto the underlying monolayer in a repeating cascading event.